Recomendaciones para la Realización de una Auditoría Efectiva de Sistemas de Forma Remota (2022)
This work aims to inform the reader of the necessary requirements to perform a remote systems audit; describe the technological tools that can be used to perform and that contribute to this work environment, applying the quality standards required by ISO 9001:2015, in order to facilitate its effectiveness; mention the guidelines in order to achieve the proposed objectives, identifying if the organization is viable or has the technological infrastructure for its realization, taking as references methodologies and recommendations of auditing firms and certifying entities It is hoped that this document will be useful and that it can guide organizations and auditors in conducting remote system audits effectively.